Evaluation of physiochemical and rheological properties of some local wheat cultivars and their relationships to baking characteristics - Sabir, Dlir Amin (Sulaimani Journal for Pure and Applied Sciences, 2018)
In order to assess the bread-making potential for different cultivars and understanding there different effects on baking quality and find out the opportunity of using the suitable cultivar for suitable end product twelve different locally wheat cultivars Ala, Aras, Azad , Bakrajow , Charmo, Hamada, Hasad, Hazha , Marf, Shaho, Sarah and Tamuz were evaluated for physiochemical, rheological and baking test properties. Chemical composition of cultivars in terms of protein, fat ,carbohydrate , moisture and ash percentages were obtained from the highest values (11.4 , 3.9 , 74.7 , 16.6 ,0.56 ) to the lowest values (5.1, 1.5, 69.7, 14.4, 0.51) respectively. While wheat and baking quality of cultivars in terms of Total wet gluten, Gluten index, Thousand grain weights, Hectoliter weights, Loaf Weight, Loaf volume and Specific loaf volume (4.2 g, 99 , 31.6g, 89.4 kg/hl, 90.6g, 236.6 cm3, 2.81 cm3/g) respectively, to the lowest (1.1 g, 28, 23.6 g 74.4 kg/ hl, 81.6 g, 133.3 (cm3), 1.51 cm3/g respectively. According to sensory evaluation characters of loaf breed quality in terms of (Volume, Crust, Color, Symmetry, Bake uniformity ,Texture, Crumb, Grain, Aroma and Taste were obtained from the highest values (12.3, 4 , 4.6 , 4.3 , 13.6 , 7.6 , 8.3 , 8.6 , 16.6 ) to the lowest values (8.6, 2.6,1.3 , 1.6 , 7.3 , 4.6,5.3 , 5.6, 11.3 ) respectively. While for Amylograph and Farinograph characteristics for cultivars flours in terms of (Water absorption ,Developing time ,Stability time ,Time to break down and Gelatinization temp) were obtained from the highest values(75.6 ,15.4 min , 17.4 min , 17.4 FU , 62.3°C ) to the lowest values (63.4 ,4.4 min , 1.6 min, 4.5 FU, 57.3 °C ) respectively. Results from this study approved that there were significantly differences between all cultivars. These results indicate that there were possibilities to select suitable cultivars for suitable end product like bread with improved baking quality.
Keywords: Wheat cultivars; Baking characteristics; Rheological properties; Gluten Index and Sensory evaluation